A protocol for amide bond formation with electron deficient amines and sterically hindered substrates. Issue 2 (20th November 2015) - Due-Hansen, Maria E.; Pandey, Sunil K.; Christiansen, Elisabeth; Andersen, Rikke; Hansen, Steffen V. F.; Ulven, Trond
Abstract : A protocol for amide coupling by in situ formation of acyl fluorides and reaction with amines at elevated temperature has been developed and found to be efficient for coupling of sterically hindered substrates and electron deficient amines where standard methods failed. Abstract : A protocol for amide coupling by in situ formation of acyl fluorides and reaction with amines at elevated temperature has been developed and found to be efficient for coupling of sterically hindered substrates and electron deficient amines where standard methods failed.